The border in the urban space: expessions of the limit between Leticia (Colombia) and Tabatinga (Brasil) (2011)
The border is more than a limit. Nevertheless, it is not possible to blur the limits in border studies. This paper shows how the limits that divide the towns of Leticia (Colombia) and Tabatinga (Brazil) are a result of the relationships between these towns and the border. This relationship is expressed spatially through symbolic mechanisms, which puts in evidence the differences between the States. These spatial expressions do not disappear with changes in the border, but cause changes in the ways they are symbolized in the territory.